The Success Rate of Pediatric In-Hospital Cardiopulmonary Resuscitation in Ahvaz Training Hospitals - Shideh Assar; Mohsen Husseinzadeh; Abdul Hussein Nikravesh; Hannaneh Davoodzadeh (Scientifica)
Research Objective. This study determined the outcome of cardiopulmonary resuscitation (CPR) after in-hospital cardiac arrest and factors influencing it in two training hospitals in Ahvaz. Method. Patients hospitalized in the pediatric wards and exposed to CPR during hospital stay were included in the study (September 2013 to May 2014). The primary outcome of CPR was assumed to be the return of spontaneous circulation (ROSC) and the secondary outcome was assumed to be survival to discharge. The neurological outcome of survivors was assessed using the Pediatric Cerebral Performance Category (PCPC) method. Results. Of the 279 study participants, 138 patients (49.4%) showed ROSC, 81 patients (29%) survived for 24 hours after the CPR, and 33 patients (11.8%) survived to discharge. Of the surviving patients, 16 (48.5%) had favorable neurological outcome. The resuscitation during holidays resulted in fewer ROSC. Multivariate analysis showed that longer CPR duration, CPR by junior residents, growth deficiency, and prearrest vasoactive drug infusion were associated with decreased survival to discharge (p<0.05). Infants and patients with respiratory disease had higher survival rates. Conclusion. The rate of successful CPR in our study was lower than rates reported by developed countries. However, factors influencing the outcome of CPR were similar. These results reflect the necessity of paying more attention to pediatric CPR training, postresuscitation conditions, and expansion of intensive care facilities.